Situational Factors Influencing Students' Willingness to Communicate - Qamaria, Nur Asisia (AL LUGHAWIYAAT, 2023)
This qualitative study investigated the situational factors influencing students’ willingness to communicate in speaking classroom. The participants of this study were 15 students majoring in the English Education at one of higher educational institutions at Kendari. The result of data analysis found some situational factors affecting students' willingness to communicate in speaking class. Three themes emerged, i.e. students’ WTC and questions, students’ WTC and opinion, students’ WTC and speaking. Various situational factors affect the students’ understanding the topic, to speak in groups and in pairs, task type, background of knowledge as indicated directly by the lecturer during the learning process. This study implies that the teacher can provide enough understanding of the factors that can make students want to communicate by themselves.